Training for sustainability in the Triple Helix: assessment of an intersectoral diploma program - Arias-Valle, María-Belén; Gámez Figueroa, Daniela Fabiana; Perez Armendariz, María Paula; Suarez, Natalia (Przegląd Krytyczny, 2025)
This study’s primary objective was to describe and explain the impact of sustainability education within the framework of university-industry-government cooperation. We evaluated an intersectoral diploma program in Corporate Social Responsibility and Sustainability, analyzing the training provided and its applicability across different economic sectors. A case study methodology combining qualitative and quantitative approaches was employed. Data were collected from 189 graduates through surveys, documentary analysis of sustainability plans designed by them, and a literature review. Results indicated that graduates positively valued the training received and the applicable tools acquired, with 85% reporting high satisfaction. While designed sustainability plans were not fully implemented, participants found the knowledge highly applicable (78%). Differences in sustainability adoption were identified by employment sector, with lower integration in the governmental sector, highlighting specific challenges. The study’s findings suggest strengthening knowledge transfer mechanisms and establishing post-training follow-up strategies to overcome implementation barriers. This research underscores the potential of intersectoral cooperation in sustainability education and its role in fostering sustainable management practices across diverse organizational contexts.